Smoke aerosol chemistry and aging of Siberian biomass burning emissions in a large aerosol chamber. (July 2018) - Kalogridis, A.-C.; Popovicheva, O.B.; Engling, G.; Diapouli, E.; Kawamura, K.; Tachibana, E.; Ono, K.; Kozlov, V.S.; Eleftheriadis, K.
Abstract: Vegetation open fires constitute a significant source of particulate pollutants on a global scale and play an important role in both atmospheric chemistry and climate change. To better understand the emission and aging characteristics of smoke aerosols, we performed small-scale fire experiments using the Large Aerosol Chamber (LAC, 1800 m 3 ) with a focus on biomass burning from Siberian boreal coniferous forests. A series of burn experiments were conducted with typical Siberian biomass (pine and debris), simulating separately different combustion conditions, namely, flaming, smoldering and mixed phase. Following smoke emission and dispersion in the combustion chamber, we investigated aging of aerosols under dark conditions. Here, we present experimental data on emission factors of total, elemental and organic carbon, as well as individual organic compounds, such as anhydrosugars, phenolic and dicarboxylic acids. We found that total carbon accounts for up to 80% of the fine mode (PM2.5 ) smoke aerosol. Higher PM2.5 emission factors were observed in the smoldering compared to flaming phase and in pine compared to debris smoldering phase. For low-temperature combustion, organic carbon (OC) contributed to more than 90% of total carbon, whereas elemental carbon (EC) dominated the aerosol composition in flaming burns with a 60–70% contribution to the total carbon mass. For all smoldering burns, levoglucosan (LG), a cellulose decomposition product, was the most abundant organic species (average LG/OC = 0.26 for pine smoldering), followed by its isomer mannosan or dehydroabietic acid (DA), an important constituent of conifer resin (DA/OC = 0.033). A levoglucosan-to-mannosan ratio of about 3 was observed, which is consistent with ratios reported for coniferous biomass and more generally softwood. The rates of aerosol removal for OC and individual organic compounds were investigated during aging in the chamber in terms of mass concentration loss rates over time under dark conditions and compared to the loss rate of EC. The latter is used as an inert tracer for estimating aerosol mechanical deposition and wall losses of the otherwise chemically conserved aerosol species. The OC/EC ratio increased with smoke aging for the flaming phase, suggesting a production/partitioning of organic compounds after emission. On the other hand, for smoldering burns OC/EC ratios decreased further with aging due to additional sinks of OC, other than those related to deposition and wall losses alone, such as evaporation of semi-volatile compounds. The chemical fingerprints of the major PM components of fresh and aged smoke found in this study are proposed to be used for the assessment of contributions from Siberian biomass burning to atmospheric pollution in source apportionment studies like those using molecular marker approaches.